Significance of Selective Protein Degradation in the Development of Novel Targeted Drugs and Its Implications in Cancer Therapy. Issue 6 (8th April 2020) - Yang, Jie; Wang, Qiaoli; Feng, Guo‐Kai; Zeng, Mu‐Sheng
Abstract: The evolution of traditional chemotherapeutic drugs to targeted drugs has led to major changes in cancer treatment. However, it remains difficult to develop effective targeted drugs that can act against "undruggable" proteins, including some well‐known oncoproteins such as KRas. Moreover, mutations of target genes limit the use of targeted drugs. Although some strategies such as RNA interference and DNA editing have been adopted to solve these problems, their clinical use remains challenging. Therefore, new strategies are urgently needed to meet the dilemmas encountered in the use of targeted drugs. As protein degradation is a rapid and well‐regulated biological process in cells, targeting protein degradation by inducing cellular protein degradation machinery, regardless of the status of the target, is an attractive idea for developing novel targeted drugs. This review summarizes recent advances in targeted protein degradation, with a focus on the current reagents and strategies used for inducing selective degradation of target proteins to provide clues for the development of novel anticancer drugs and cancer therapies. Abstract : Selective protein degradation is a promising strategy for antitumor drug development, which overcomes the shortcomings of traditional targeted drugs‐based cancer therapy. This strategy suppresses cancer progress by selectively inducing the degradation of "undruggable" proteins as well as the "druggable" proteins with drug‐resistant mutations. This review summarizes the recent advances of selective protein degradation in antitumor drug development.